2013
DOI: 10.5194/acp-13-3271-2013
|View full text |Cite
|
Sign up to set email alerts
|

The role of the global cryosphere in the fate of organic contaminants

Abstract: Abstract. The cryosphere is an important component of global organic contaminant cycles. Snow is an efficient scavenger of atmospheric organic pollutants while a seasonal snowpack, sea ice, glaciers and ice caps are contaminant reservoirs on time scales ranging from days to millennia. Important physical and chemical processes occurring in the various cryospheric compartments impact contaminant cycling and fate. A variety of interactions and feedbacks also occur within the cryospheric system, most of which are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 240 publications
0
97
0
Order By: Relevance
“…The frozen soils of permafrost have historically been considered a barrier to the movement of contaminants and many waste and dump sites use containment strategies that rely on the low mobility of contaminants in permafrost soils (Grannas et al, 2013). However, the warming Arctic climate may lead to an increased mobility of contaminants, either stored in soils at waste sites or historically accumulated in permafrost, into Arctic surface waters (Armitage and Wania, 2013;Chételat et al, 2014).…”
Section: Mobilization Of Contaminantsmentioning
confidence: 99%
“…The frozen soils of permafrost have historically been considered a barrier to the movement of contaminants and many waste and dump sites use containment strategies that rely on the low mobility of contaminants in permafrost soils (Grannas et al, 2013). However, the warming Arctic climate may lead to an increased mobility of contaminants, either stored in soils at waste sites or historically accumulated in permafrost, into Arctic surface waters (Armitage and Wania, 2013;Chételat et al, 2014).…”
Section: Mobilization Of Contaminantsmentioning
confidence: 99%
“…They also suppress photochemical reactions by acting as a filter of light and by scavenging reactive species (Grannas et al, 2007b). The environmental importance of organic compounds in ice is discussed in detail by McNeill et al (2012) and Grannas et al (2013). Abida and Osthoff (2011) recently reported that organic co-solutes ranging from formate to phenol inhibited the release of gasphase NO 2 from nitrate photolysis in ice, likely due to scavenging of OH.…”
Section: Chemical Environmentsmentioning
confidence: 99%
“…In this review, we focus on atmospheric and cryospheric science of the polar regions, where chemistry and physical processes in snow have a far-ranging environmental impact (Grannas et al, 2013). The focus was placed on studies that showed the interplay of impurities with snow and ice and that characterised the structural environment down to a molecular level.…”
Section: Synthesis and Outlookmentioning
confidence: 99%
See 2 more Smart Citations